Family members’ experiences with the spiritual care of older people living with dementia in nursing homes: A phenomenological hermeneutical study - Nataša Mlinar Reljić; Zvonka Fekonja; Sergej Kmetec; Wilfred McSherry; Blanka Kores Plesničar; Majda Pajnkihar (Nursing Open, 2021)
Abstract Aim To illuminate family members experiences with the spiritual care provided to their family members living with dementia in nursing homes. Design A qualitative research design utilizing phenomenological hermeneutical approach. Methods Data were gathered by conducting twelve in‐depth interviews with family members of older people living with dementia in nursing homes and analysed using the phenomenological hermeneutical analysis. The COREQ guidance was used for reporting of this study. Results Finding revealed that family members were worried and fearful when nursing care was routinely provided with little consideration given to spiritual needs and lacking compassion. Findings affirm that “riendliness” is an essential aspect of respectful caring from the family members' perspective. Family members want compassionate, loving, caring and dignified nursing care for their relative living with dementia in the nursing homes.